Thrombocytopenia in Critically Ill Children: A Review for Practicing Clinicians - Balagangadhar R. Totapally; Abhinav Totapally; Paul A. Martinez (Children)
Thrombocytopenia frequently occurs in patients before, during, and after admission to Pediatric Intensive Care Units (PICUs). In critically ill children, it is often due to multifactorial causes and can be a sign of significant organ dysfunction. This review summarizes the potential causes/mechanisms of thrombocytopenia in acutely ill children, their identification, and treatments, with special attention paid to septic patients. The mechanisms of thrombocytopenia include decreased production and sequestration, but the most common reason is increased destruction or consumption. This review specifically reviews and compares the presentation, pathogenesis, and treatment of disseminated intravascular coagulation (DIC) and the thrombotic microangiopathic spectrum (TMA), including thrombocytopenia-associated multiorgan failure (TAMOF), hemolytic uremic syndrome, and other diagnoses. The other etiologies discussed include HLH/MAS, immune thrombocytopenia, and dilutional thrombocytopenia. Finally, this review analyzes platelet transfusions, the various thresholds, and complications.